(3eMGSHI TQcGJ GdCehGds - (3jhSa eUWai(B, (3SYGOIs ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2002)
(3GdJYQja HGdTQcGJ GdeSGgeI hEOGQJgG,JbOje QCS GdeGd Jehjd GdTQcI GdeSGgeI,GdJehjd HGdEbJQGV GdSfOGJ hGdJCLjQ,GdGSJKeGQGJ aj GdCSge hGdSfOGJ bUjQI hWhjdI GdCLd,GdMSGHGJ GdNJGejI hGdbhGFe GdeGdjIddTQcGJ GdeSGgeI,bGFeI GdJOabGJ GdfbOjI eUGOQ GdCehGd hGSJNOGegG,GfbVGA TQcGJ GdCehGd,CfhGY CNQi ef GdTQcGJ GdeSGgeI GdTQcI PGJ GdeSDhdjI GdeMOhOI hTQcI GdJhUjI HGdCSge,CfhGY CNQi ef GdTQcGJ GdTQcGJ GdeOfjI (B((3GdTQcGJ YfO GdeSdejf,JMhd GdTQcGJ hNUNUJgGs
(3HHdjhZQGajG(B:(3U(B.429-434s
Keywords: (3GdTQcGJ(B-(3eMGSHIs